Nanomedicine-mediated alteration of the pharmacokinetic profile of small molecule cancer immunotherapeutics - Herck Simon Van; Geest Bruno G. De (Acta Pharmacologica Sinica, 2020)
The advent of immunotherapy is a game changer in cancer therapy with monoclonal antibody- and T cell-based therapeutics being the current flagships. Small molecule immunotherapeutics might offer advantages over the biological drugs in terms of complexity, tissue penetration, manufacturing cost, stability, and shelf life. However, small molecule drugs are prone to rapid systemic distribution, which might induce severe off-target side effects. Nanotechnology could aid in the formulation of the drug molecules to improve their delivery to specific immune cell subsets. In this review we summarize the current efforts in changing the pharmacokinetic profile of small molecule immunotherapeutics with a strong focus on Toll-like receptor agonists. In addition, we give our vision on limitations and future pathways in the route of nanomedicine to the clinical practice.